Linguistic features of animal color names in phraseologisms (Eurasian Journal of Philology Science and Education, 2020)
As you know, the study of unrelated languages, in particular Kazakh and English, is one of the areas in domestic linguistics, which has been actively developing in recent years. An important issue will be the consideration in the linguistic picture of the world of phraseological units with zoomorphisms and zoocomponents that occur in our language and demonstrate economic activities that reflect the life and life experience of the nation. Special attention is paid to the study and determination of the value of each nation, considering phraseological combinations with color names of animals found in the Kazakh and English languages, their similarities and differences. In our research, the specific significance of determining the identity and features of phraseological units in the Kazakh and English languages is obvious. In general, the problem considered in our study is that any language, along with its original counterparts, has its own characteristics and is directly related to the knowledge, life, culture and customs of each nation. As you know, these repercussions are felt in the language. Not to mention some language elements in one language, especially in the second language of the color we are considering, that is, it may cause difficulties in transmitting the equivalent in English. This also indicates that each language has its own specific features and properties, and this should not be forgotten.